Faktor Penyebab Stunting di Puskesmas Pembantu Rumah Tumbuh Kabupaten Muara Enim - Ferdianda Dwi Yuda; Erfan Ramadhani; Nurlela Nurlela (Journal on Education, 2024)
This research aims to identify the factors that cause stunting in the Muara Enim Regency Home Growth Community Health Center, with a focus on Sukarami Village, Muara Enim District, South Sumatra Province. A qualitative approach was used involving Community Health Center officers, parents of stunted children, and community members around the Community Health Center as research informants. Sampling was carried out through purposive sampling to ensure the existence of relevant information. The research results show that factors such as low levels of maternal education, family economic conditions, limited access to health services, and unhealthy eating habits are the main contributors to the high prevalence of stunting. It was also found that efforts to overcome stunting require a holistic and integrated approach from the government, community and family. This research also highlights the need to increase the accessibility of health services, improve the socio-economic conditions of families, and implement sustainable education and counseling programs. As a result, a comprehensive intervention strategy was proposed to overcome stunting in the region. These findings can make a significant contribution to increasing public understanding about stunting and supporting government policies in achieving public health rights in accordance with the mandate of the Preamble to the 1945 Constitution of the Republic of Indonesia.